Peran Tata Usaha Dalam Meningkatkan Layanan Administrasi Di SMP Negeri 9 Palembang - Laili Nurfadillah; Ade Akhmad Saputra (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to examine the role of the administrative office in improving administrative services at SMP Negeri 9 Palembang. This study employs a qualitative approach using the case study method. Data were collected through interviews, observations, and documentation involving the principal, the head of the administrative office, administrative staff, teachers, and students. The research findings indicate that school administrative staff play a key role in improving school administrative services across five dimensions of service quality: physical evidence, reliability, responsiveness, assurance and empathy. In terms of physical evidence, the school already has adequate administrative facilities, although there are still some shortcomings in terms of infrastructure. In terms of reliability, the administrative staff have carried out their duties in an orderly and meticulous manner, in accordance with procedures. In terms of responsiveness, the administrative staff are quite quick to respond to the administrative needs of the school community. In terms of reliability, the administrative staff demonstrate a professional, polite and responsible attitude. In terms of empathy, the administrative staff are able to provide a friendly and patient service, whilst paying close attention to the needs of service users. The challenges that remain include limited facilities, the use of personal devices by staff, limited archive space, and the need to improve the skills of administrative staff. Consequently, the school administration plays a significant role in ensuring the smooth running of school administrative services.